PENDAMPINGAN BIMBINGAN BELAJAR SISWA SEKOLAH MENENGAH PERTAMA SELAMA PANDEMI COVID-19 DI RT 05 KELURAHAN BAJAK PROVINSI BENGKULU - Ririn Rahmayanti; Yanti Paulina; Eli Rustinar; Reni Kusmiarti (Almaun: Jurnal Pengabdian Kepada Masyarakat, 2023)
The existence of the Covid-19 pandemic has brought many changes in human life. One area of ​​human life that also feels the impact of this is in the field of education. The Covid-19 pandemic has become one of the obstacles for children who experience difficulties with online learning, such as in making assignments, not understanding the material delivered by the teacher, learning tends to be online assignments, and the difficulty of the internet network, especially for children who exist in the villages. Various efforts have been made to overcome the problems that occur, one of which is through the Tutoring Assistance program. The method used in this service is guidance. The guidance used is tutoring that emphasizes assisting junior high school students. This study assistance is a form of contribution in the field of community service. Community service activities aim as a means to channel the knowledge and concern they have for children who are currently undergoing their school period. In this service research the focus is on junior high school students in RT 05 Bajak Village. Based on the results of the dedication of tutoring activities, it can help parents who cannot accompany their children in participating in online learning for students and also to increase the learning motivation of junior high school students who live in RT 05, Bajak Village, Bengkulu Province